Islam Gender dan Feminisme Dalam Al-Quran - Mubarakh, M Alfatih; Akhlasa, Rindah; Al Faiz, Wafi Athallah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the concept of gender equality in Islam through an analysis of feminism and maudhui’ interpretation of the verses of the Qur’an. This study focuses on how Islamic feminism interprets verses related to gender, such as Q.S. An-Nisa 3, 11, 12, and 34 which discuss justice in marriage, inheritance, and household leadership. In addition, Q.S. Ali ‘Imran 195 and Al-Qiyamah 37-39 emphasize that human creation is equal without gender hierarchy. Modern interpretations from figures such as Amina Wadud and KH. Husain Muhammad emphasize the need for a contextual approach and reinterpretation of verses that are often understood patriarchally. This study aims to provide an alternative perspective on gender relations in Islam and open up space for a more inclusive understanding in accordance with the values of justice.